2022
DOI: 10.3390/jcm11216481
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Ustekinumab for Moderate to Severely Active Crohn’s Disease: Results from an Early Access Program in Brazil

Abstract: This prospective, observational, open-label study aimed to provide access to ustekinumab prior to market authorization and assess its safety and effectiveness in patients with Crohn’s disease (CD) refractory to anti-tumor necrosis factor-α and conventional drugs in Brazil. Patients with a diagnosis of moderate-to-severe active CD for ≥ 3 months before screening received ustekinumab in a single intravenous induction dose (~6 mg/kg) at week 0, and a 90 mg maintenance dose, subcutaneously, every 8 or 12 weeks, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These studies were however restricted by a retrospective design and follow-up data beyond 52 weeks was available in only a small number of patients. Recently, a small prospective study showed persistency rates of 77% at week 80 with clinical remission in 88% of these patients and endoscopic improvement in 63% of patients with a follow-up endoscopy [22]. Furthermore, a recent prospective study described outcomes at 104 weeks for 252 Crohn’s disease patients initiated on ustekinumab with a similar design as our study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…These studies were however restricted by a retrospective design and follow-up data beyond 52 weeks was available in only a small number of patients. Recently, a small prospective study showed persistency rates of 77% at week 80 with clinical remission in 88% of these patients and endoscopic improvement in 63% of patients with a follow-up endoscopy [22]. Furthermore, a recent prospective study described outcomes at 104 weeks for 252 Crohn’s disease patients initiated on ustekinumab with a similar design as our study.…”
Section: Discussionmentioning
confidence: 57%
“…Corticosteroid-free remission rates after 52 weeks ranged from 12.2 to 47.4% [6,9,13,17,18]. Long-term outcomes beyond 52 weeks have only been assessed in a few real-world studies which were often restricted by small numbers or a retrospective design [19][20][21][22]. Recently, a large Dutch prospective cohort study reported a corticosteroid-free clinical remission rate of 34% at week 104 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a Brazilian prospective study, the UST discontinuation rate was 23% which is closer to our results of drug sustainability. Their treatment was also well tolerated during the 80 weeks of follow-up, though they mention a serious adverse event rate of 21% with mostly infectious causes 23 . Comparing these results of the different studies is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The post‐marketing surveillance in Japan ( 63 ) shown that the overall incidences of ADRs and SADRs were 5.3% and 2.1%, respectively. A study in Brazil shown that, although most of patients might experience at least one AE, most of the AEs were mild or moderate and were not connected to the UST, with the SAE rate being 21% and with the ADR rate being 44% ( 64 ). A prospective cohort study conducted in The Netherlands ( 65 ) revealed that the ADRs associated with UST were 13.4 per 100 patient-years, and only 7% of patients discontinued UST due to ADRs.…”
Section: Clinical Applications Of Ustmentioning
confidence: 99%